Impact Analysis of Beam-Hardening CT-Artefacts in Radiotherapy planning - Starenkij, V. P.; Vasyliev, L. L.; Samofalov, I. O.; Trofymov, A. V. (Problems of Atomic Science and Technology, 2016)
The methods of X-ray computed tomography being improved every year and we have a sufficient amount of methods and tools for high-quality visualization at that very moment. However, as practice shows, there are still low quality CTs (with the presence of strongly pronounced artifacts) in the developing countries. The quality of the scans is of great importance in radiotherapy planning. An incorrect mapping of the density distribution will distort isodosescalculation. In the present article, we will consider the impact magnitudes of the beam hardening artifacts on the radiotherapy planning
Keywords: radiotherapy planning,CT, artifact